Situation Report: Romania, 4 May 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu's Speech at the April CC Plenum: Ideological Aspects / by Michael Shafir Romania Pays Off Foreign Debts and Will Note Take Out New Ones / by Paul Gafton Territorial Reorganization Approved / by Dan Ionescu Ceausescu Claims that Romania Could Make Nuclear Weapons / by Vladimir Socor Romania in the Dock: Persecution of Dissidents and Other Violations of Human Rights / by Mihai Sturdza Doina Cornea Criticizes Ceausescu Again / by Crisula Stefanescu Mircea Dinescu's Letter of Protest to the Chairman of the Writers' Union / by Crisula Stefanescu Seven Intellectuals Protest against Dismissal of Mircea Dinescu / by Crisula Stefanescu